2008
DOI: 10.1007/s00101-008-1379-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotikatherapie bei operativen Intensivpatienten

Abstract: The development of resistance by infective bacterial species is an incentive to reconsider the indications and administration of available antibiotics. Correct recognition of the indications and duration of therapy are particularly important for the use of highly potent substances in the intensive care situation. There has as yet been no clinical chemical parameter which is capable of specifically distinguishing a bacterial infection from a viral or non-infectious inflammatory reaction, but it now appears that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
0
10
1
4
Order By: Relevance
“…This approach was mainly evaluated in patients with respiratory tract infections; however, it can also be used in critically ill patients with sepsis or severe sepsis of various origins [3, 4, 5, 6, 7]. In addition, in outpatients with respiratory tract infection and exacerbation of chronic obstructive pulmonary disease (COPD), antibiotic prescription rates were significantly reduced by the use of PCT [8, 9].…”
Section: Procalcitonin (Pct) As a Marker For The Diagnosis Of Sepsis mentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was mainly evaluated in patients with respiratory tract infections; however, it can also be used in critically ill patients with sepsis or severe sepsis of various origins [3, 4, 5, 6, 7]. In addition, in outpatients with respiratory tract infection and exacerbation of chronic obstructive pulmonary disease (COPD), antibiotic prescription rates were significantly reduced by the use of PCT [8, 9].…”
Section: Procalcitonin (Pct) As a Marker For The Diagnosis Of Sepsis mentioning
confidence: 99%
“…Specific indications like treatment of endocarditis or severe bone infection are excluded from this rule. Various studies indicate that a maximum duration of treatment of approximately seven days is enough to treat even a severe focus of bacterial infection or sepsis [3, 5, 6, 51, 52]. …”
Section: Practical Approachmentioning
confidence: 99%
“…In dieser Studie konnte eine Reduktion der Antiobiosedauer um ca. 2 Tage erreicht werden ohne den klinischen Erfolg zu verschlechtern [38] . Die Bedeutung der PCT-Verlaufsmessungen wurde auch bei Intensivpatienten mit Sepsis und bestehender empirischen antibiotischen Therapie untersucht [39] .…”
Section: Klinische Anwendung Der Pct-spiegel Infektionsmarkerunclassified
“…Hochreiter and Schröder showed that, in the case of adequate antibiotic therapy, PCT levels decrease significantly after 4 days [9]. In addition, Charles et al demonstrated that a lack of PCT reduction on day 3, compared with day 2 of antibiotic therapy, is a resilient indicator of inadequate treatment (OR = 10.29) [10].…”
Section: Introduction and Objectivesmentioning
confidence: 99%